Cardio - and neuroprotective effects of alpha cyclodextrin / moringin complex in sprague dawley rats with isoproterenol- induced myocardial infarction - Kamal, Ramla Muhammad (2023)
Myocardial infarction (MI) is a severe form of coronary artery disease resulting from ischemic pathological changes of the myocardium. MI presents with signs of heart and brain affectation, but these are treated independently with different drugs. There is need for alternative treatment options that can target both cardiovascular and behavioral alterations due to MI. Isothiocyanates (ITCs) are bioactive compounds resulting from myrosinase catalyzed hydrolysis of glucosinolates (GLs). ITCs are derived from plants and have been shown to protect the heart and brain from oxidative stress in various cardiovascular and neuronal diseases’ models. In previous studies, ITCs normalized hemodynamic variables, behavior as well as heart and brain redox status and morphology. Moringa oleifera Lam. seeds are rich in glucomoringin (a GL) the precursor of moringin (an ITC). The cardio- and neuroprotective effects of the ITC moringin (MG) as well as its novel formulation (alpha-cyclodextrin/moringin complex (α- CD/MG)) have not been studied on MI. M. oleifera was chosen because of its powerful antioxidant and cardioprotective effects and is believed to provide benefits in MI. This study was designed to investigate the potential of MG and α-CD/MG in protecting the heart and brain against MI-induced oxidative stress in isoproterenol-induced MI rat model. MG obtained from myrosinase catalyzed bioactivation of glucomoringin (GMG) isolated from M. oleifera seeds, was characterized with high performance liquid chromatography (HPLC) and nuclear magnetic resonance spectroscopy (NMR). Similarly, newly formulated α-CD/MG was characterized using one- and two-dimensional NMR. HPLC revealed successful bioactivation of GMG to MG after 15 min of incubation at 37 ℃ while NMR confirmed the molecular structures of MG and α-CD/MG. Male Sprague Dawley rats were grouped into 4 groups of eight. MG and α-CD/MG groups were respectively pretreated via oral gavage with MG and α-CD/MG at 20mg/kg and 42 mg/kg body weight diluted in 2 ml phosphate buffered solution (PBS) for seven days. While control and MI groups received only PBS. In the last two days of pretreatment, MI was induced by the subcutaneous administration of isoproterenol hydrochloride (85 mg/kg body weight) in 2 ml of normal saline 24 hr apart. Induction of MI in rats was successful as confirmed with serum diagnostic cardiac markers. Data were analyzed and presented as mean ± standard error of means. The difference between means was determined using one-way analysis of variance (ANOVA), and the level of significance was reported at p≤0.05. Pretreatment of rats with MG and α-CD/MG significantly modified hemodynamic alterations, behavior, heart and brain oxidative stress and architectural distortions compared to vehicle-pretreated MI rats. Non-invasive CODA readings showed significant modification in tachycardia (heart rate of 345±15 vs 466±4) and hypotension (systolic blood pressure 115±3 vs 77±2) while Open Field Test (OFT) parameters revealed reduced anxiety-like behaviors (number of lines crossed 29 vs 8) in α-CD/MG compared to vehicle-pretreated MI rats. Significant difference in serum cardiac troponin I (270±1.46 vs 407±0.52) and creatine kinase-MB (93±2.16 vs 155 ±7.58), hippocampal dopamine (2.35±0.27 vs 0.88±0.04) and serotonin (0.4 ±0.02 vs 0.25±0.02) levels, oxidative stress markers as well as microscopic abnormalities were favorably modified with α-CD/MG pretreatment compared to vehicle-pretreated MI rats. Conclusively, and for the first time MG and α-CD/MG exhibited significant suppression of myocardial and brain oxidative stress evidenced by alleviation of behavioral, hemodynamic, biochemical, and histological alterations from isoproterenol-induced MI. Hence, α-CD/MG appears to be a novel alternative in the prevention of cardiovascular and behavioral manifestations of MI. Nonetheless, there is need for further studies to gain more insight into the mechanism of action of α-CD/MG in MI.